2016
DOI: 10.1080/2162402x.2016.1232221
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-associated neutrophils display a distinct N1 profile following TGFβ modulation: A transcriptomics analysis of pro- vs. antitumor TANs

Abstract: It is becoming increasingly clear that tumor-associated neutrophils (TANs) play an important role in cancer biology, through direct impact on tumor growth and by recruitment of other cells types into the tumor. The function of neutrophils in cancer has been the subject of seemingly contradicting reports, pointing toward a dual role played by TANs in tumor progression. The existence of multiple neutrophil subsets, as well as phenotypic modulation of the neutrophils by various factors in the tumor microenvironme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
250
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(259 citation statements)
references
References 58 publications
7
250
0
2
Order By: Relevance
“…In their review on TANs as targets for cancer therapy , Gregory and Houghton raised the interesting question whether the differences between N1 and N2 TANs were due to two unique transcriptional programs as suggested in our work or instead represented two states of activation, that is, that N1 TANs produce the same mediators, but at different levels. In our recently published transcriptomic comparison between N1 and N2 TANs, we found that a vast majority of the changes were indeed upregulation of the same genes and pathways in N1 TANs compared to N2 TANs . However, there were some clear exceptions.…”
Section: Tumor‐associated Neutrophilsmentioning
confidence: 70%
“…In their review on TANs as targets for cancer therapy , Gregory and Houghton raised the interesting question whether the differences between N1 and N2 TANs were due to two unique transcriptional programs as suggested in our work or instead represented two states of activation, that is, that N1 TANs produce the same mediators, but at different levels. In our recently published transcriptomic comparison between N1 and N2 TANs, we found that a vast majority of the changes were indeed upregulation of the same genes and pathways in N1 TANs compared to N2 TANs . However, there were some clear exceptions.…”
Section: Tumor‐associated Neutrophilsmentioning
confidence: 70%
“…Importantly, aside from their well-described role in host defenses, accumulating evidence indicate that neutrophils exhibit a high phenotypic and functional plasticity depending upon TGFβ available in the TME (117). Indeed, similar to macrophages, TGFβ has been shown to drive the phenotype change of a more tumor cytotoxic and pro-inflammatory phenotype (N1) into a tumor supportive phenotype (N2) (113).…”
Section: Tgfβ As a Central Regulator Of Rt-induced Tumor Immunogenicitymentioning
confidence: 99%
“…Through an extensive time course (24,48, 72 hours, 7, and 28 days) characterization of this model, we observed a significant neutrophil influx within the peritoneal fluid early (24-72 hours) after surgical induction of endometriosis compared to sham-operated controls. Through an extensive time course (24,48, 72 hours, 7, and 28 days) characterization of this model, we observed a significant neutrophil influx within the peritoneal fluid early (24-72 hours) after surgical induction of endometriosis compared to sham-operated controls.…”
Section: Discussionmentioning
confidence: 85%
“…Through an extensive time course (24,48, 72 hours, 7, and 28 days) characterization of this model, we observed a significant neutrophil influx within the peritoneal fluid early (24-72 hours) after surgical induction of endometriosis compared to sham-operated controls. 18,24,44 Early neutrophil recruitment was associated with elevated peritoneal fluid inflammatory cytokines (TNF-α, IL-6, IL-4), neutrophil chemokines (G-CSF, CXCL1), and the angiogenic growth factor, VEGF, which have been previously associated with endometriosis. Nonetheless, this rapid innate response of neutrophils is seen in various models of sterile tissue injury and repair, and further highlights the potential for refluxed endometrial debris to serve as a mediator of sterile inflammation.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation